The influence of price perception, location, and service quality at Indomaret Madura Pamekasan on customer loyalty through satisfaction as a mediating variable - Halimatus Zahroh; Albari Albari (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to explain the positive influence of perceived price, location and service quality on customer satisfaction and customer loyalty. Testing in this study used 381 respondents. The sampling technique used in this research was convenience sampling. This research uses the Structural Equation Modeling (SEM) analysis tool which was developed to test research hypotheses which were processed using the AMOS version 21 program. The variables used in this research are perceptions of price, location, service quality, customer satisfaction and customer loyalty. And the results of the analysis in this research show that perceptions of price, location and service quality have a positive and significant influence on customer satisfaction and customer loyalty. Customer satisfaction also has a positive influence on customer loyalty.